ANALISIS EFEKTIVITAS RADIATOR PADA MESIN TOYOTA KIJANG TIPE 5 K - David Fraim Simamora; Frans Palobo Sappu; Tertius V Y Ulaan (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2015)
Â ABSTRACT The Function of a radiator on the car engine is to cool down the cooling fluid which arbsorbed the heat from the engine. Subsequently the heat is transferred to the air that drawned by a fan. This research aim is to calculate the efectivity of a radiator during the effort of the cooling process on the engine of Toyota Kijang type 5 K, so the engine can optimally work. This research is done at the condition of idle rotation, by recording the number of the engine rotation , the temperature of drawn and leaving the radiator. Base on the results of we may concluded that radiator works efective on the cooling process with the rotation of 1700 rpm with the efectifity number is 0.502, at rotation of 2000 rpm the efectifity number is 0.52 and at rotation of 2500 rpm the efectifity number is 0.584. Keywords : radiator, engine rotation (n), effectiveness (Ïµ).